Response surface model based emission source contribution and meteorological pattern analysis in ozone polluted days. (15th August 2022) - Chen, Ying; Zhu, Yun; Lin, Che-Jen; Arunachalam, Saravanan; Wang, Shuxiao; Xing, Jia; Chen, Duohong; Fan, Shaojia; Fang, Tingting; Jiang, Anqi
Abstract: Urban and regional ozone (O3 ) pollution is a public health concern and causes damage to ecosystems. Due to the diverse emission sources of O3 precursors and the complex interactions of air dispersion and chemistry, identifying the contributing sources of O3 pollution requires integrated analysis to guide emission reduction plans. In this study, the meteorological characteristics leading to O3 polluted days (in which the maximum daily 8–h average O3 concentration is higher than the China Class II National O3 Standard (160 μg/m 3 )) in Guangzhou (GZ, China) were analyzed based on data from 2019. The O3 formation regimes and source apportionments under various prevailing wind directions were evaluated using a Response Surface Modeling (RSM) approach. The results showed that O3 polluted days in 2019 could be classified into four types of synoptic patterns (i.e., cyclone, anticyclone, trough, and high pressure approaching to sea) and were strongly correlated with high ambient temperature, low relative humidity, low wind speed, variable prevailing wind directions. Additionally, the cyclone pattern strongly promoted O3 formation due to its peripheral subsidence. The O3 formation was nitrogen oxides (NOx )-limited under the northerly wind, while volatile organic compounds (VOC)-limited under other prevailing wind directions. Anthropogenic emissions contributed largely to the O3 formation (54–78%) under the westerly, southwesterly, easterly, southeasterly, or southerly wind, but only moderately (35–47%) under the northerly or northeasterly wind. Furthermore, as for anthropogenic contributions, local emission contributions were the largest (39–60%) regardless of prevailing wind directions, especially the local NOx contributions (19–43%); the dominant upwind regional emissions contributed 12–46% (e.g., contributions from Dongguan were 12–20% under the southeasterly wind). The emission control strategies for O3 polluted days should focus on local emission sources in conjunction with the emission reduction of upwind regional sources. Graphical abstract: Image 1 Highlights: Meteorological patterns associated with O3 polluted days in Guangzhou were characterized. O3 source contribution under various prevailing wind directions was analyzed using RSM. O3 formation was NOx -limited under north wind while VOC-limited under other wind. Local emission control is a priority for alleviating O3 pollution in Guangzhou. Emission control of upwind regional emissions further lowers ambient O3 .